Integrative Language Skills: A Theoretical Analysis of Receptive and Productive Components - R. Tamtam Kamaluddin (PT FORMOSA CENDEKIA GLOBAL, 2026)
Comprehensive language skills—comprising listening, speaking, reading, and writing—constitute the primary foundation of human communication and cognitive development. However, in pedagogical implementation, these four skills are often taught in isolation (partially). This study aims to theoretically and conceptually examine the integrative relationship among the components of language skills and its implications for language learning models. The research method employed is a literature review (library research) by collecting, reducing, and analyzing data from relevant textbooks, scientific journals, and curriculum documents. The results of the literature analysis indicate that receptive skills (listening and reading) act as the primary stimulus (input) that determines the quality of productive skills (speaking and writing) as the output. This study concludes that language teaching approaches must shift from a linear-partial model toward an integrative-holistic model to cultivate meaningful language proficiency.